'Be true to yourself': Transnational mobility, identity, and the construction of a mobile self by Taiwanese young adults. Issue 3 (4th May 2022) - Huang, Shuling
ABSTRACT: Adopting Salazar's 'imaginaries of mobility, ' this paper investigates how transnational mobility becomes imaginable, desirable or even experientially imperative for mobile Taiwanese young adults in the context of globalisation. It analyses the ways by which they interpret their mobilities as a pursuit of self-identity while negotiating the tensions between collectivism and individualism of Taiwanese society. Based on personal profiles and self-narratives of mobility appearing on a Taiwanese media website devoted to the topic of transnational mobility, I demonstrate how writers present a 'mobile self' characterised by being geographically mobile, socially transgressive and culturally cosmopolitan. This self is depicted in sharp contrast with the immobile at home and narrated as an integral part of achieving identity through three kinds of self-transformation: becoming true to oneself, becoming independent, and becoming a dreamer. While these narratives resonate Western discourses of mobility, they are interpreted from the lens of individualism-collectivism opposition in East Asia and of generational conflicts in Taiwan. Specifically, transnational mobility, regardless forms, is framed as a generational revolt against a collectivist society that represses individuality. The results show how imaginaries of mobility are recontextualised, producing meaning and practice based on local references.